Innovations in Teaching: A Case of Using Kinesthetic Learning Activity for Teaching Physics (Indian Journal of Extension Education, 2023)
The paper evaluates the advantage of the role of Kinesthetic Learning Activity (KLA) method in understanding basic concepts of physics over traditional methods. This study was conducted during the year 2022-23. The topic “Photo-electric effect” of grade 12 was selected for KLA from feedback of 20 teachers and literature study. A sample of 50 students from two schools in Kolkata was taught the topic traditionally. Later the Kinesthetic learning activities were conducted in the classroom and school field. The data of pre KLA and post KLA were collected and analyzed using various statistical tools using SPSS software. The calculated value of t in paired t-test was 21.289 with p values 0.000 which clearly showed differences in pre and post-KLA and were highly significant. Ninety percent of the respondent students showed high satisfaction with KLA. Major improvement in post-KLA score was observed which increased from an average value of 8.00 to an average value of 15.12. Thus it is concluded that KLA was very effective in teaching the target topic. The learning from this study may be applicable across the disciplines including the field of agriculture extension to make an effective understanding of abstract topics in informal settings also.